Combined brain-derived neurotrophic factor and neurotrophin-3 treatment is preferred over either one separately in the preservation of the auditory nerve in deafened guinea pigs - Vink, Henk A.; Ramekers, Dyan; Thomeer, Hans G. X. M.; Versnel, Huib (Frontiers in Molecular Neuroscience, 2022)
Severe hearing loss or deafness is often caused by cochlear hair cell loss, and can be mitigated by a cochlear implant (CI). CIs target the auditory nerve, consisting of spiral ganglion cells (SGCs) which degenerate gradually following hair cell loss. In animal models it has been established that treatment with the neurotrophins brain-derived neurotrophic factor (BDNF) and neurotrophin-3 (NT-3) reduce SGC degeneration. In this study, we aimed to investigate whether treatment with both BDNF and NT-3 (Cocktail) is superior to treatment with each neurotrophin separately regarding cell preservation and neural responsiveness to electrical stimulation. To this end deafened guinea pigs received neurotrophic treatment in their right ear via gelatin sponge on the perforated round window membrane, followed by cochlear implantation four weeks later in the same ear for electrophysiological recordings to various stimulation paradigms. Normal-hearing and deafened untreated guinea pigs were included as positive and negative controls respectively. Substantial SGC loss occurred in all deafened animals. Each of the neurotrophic treatments led to enhanced SGC survival mainly in the basal turn of the cochlea, gradually decreasing towards the apex. The Cocktail treatment resulted in the highest SGC survival in the treated ear, followed by BDNF, with the least protection of SGCs following NT-3 treatment. Survival of the SGC’s peripheral processes (PPs) followed the same trend in response to the treatment. However, survival of SGCs and PPs in the contralateral untreated ears was also highest in the Cocktail group. Consequently, analysis of the ratio between the treated and untreated ears showed that the BDNF group, which showed low SGC survival in the untreated ear, had the highest relative SGC survival of the three neurotrophin-treated groups. Neurotrophic treatment had positive effects in part of the electrically evoked compound action potential recording paradigms. These effects were only observed for the BDNF or Cocktail treatment. We conclude that treatment with either BDNF or a cocktail of BDNF and NT-3 is preferred to NT-3 alone. Furthermore, since the Cocktail treatment resulted in better electrophysiological responsiveness and overall higher SGC survival than BDNF alone, we are inclined to recommend the Cocktail treatment rather than BDNF alone.